The Work-from-Home Experience of Bank Employees During COVID 19 Pandemic in Nigeria: Insights into Workplace Factors - Chovwen, Chatherine O.; Adu, Richard Akinjide; Jemirade, Benjamin (PYC Nepal Journal of Management, 2024)
In the aftermath of the national lockdown triggered by the COVID-19 pandemic, working from home (WFH) emerged as a preferred option for many organizations. This study employed a cross-sectional survey design using an online questionnaire to assess the impact of workplace factors: job satisfaction (JS), organizational citizenship behaviors (OCB), and employee motivation (EM) on the WFH experience of purposively selected bank employees in Lagos, Nigeria. Standardized scales with strong psychometric properties were used to measure the study variables, and data were analyzed using appropriate statistical methods. The results showed that JS and EM had a significant positive influence on bankers’ WFH experience, whereas OCB did not have a notable impact. Furthermore, the combined influence of JS, OCB, and EM contributed meaningfully to employees’ overall WFH experience. Recognizing the importance of these factors can help enhance employee productivity in remote work settings. The study recommends implementing intervention programs aimed at improving JS, EM, and OCB to optimize the WFH experience for bank employees.